2011
DOI: 10.33899/rjs.2011.31232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Effective Microorganisms (EM) in Blood Sugar Contrition and Some Biochemical Parameters in Normal and Alloxan Induced Diabetic Male Rats

Abstract: This study was designed to examine the effect of Effective Microorganisms (EM) in the levels of glucose, cholesterol, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL), vary low density lipoprotein (VLDL), alanine amenotransferase (ALT), aspartate amenotransferase (AST) in normal and alloxan-induced diabetic rats and these results were compared with the effect of Glibenclamide as control chemical drug. The results of this study showed that diabetes mellitus induced by alloxan for 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The results of Table (4) showed a significant increase (P≤0.05) in the activity of the enzyme aminotransferase enzyme in the group of experimental diabetic rats (B), which reached 46.33 IU/l, compared with the intact control group (A), which was 21.67 IU/l, these results were consistent with what was mentioned by Mohammed et al, (2011) when they indicated a significant increase in the activity of the ALT enzyme compared to the intact control group. The cause of the increase in diabetic rats may be attributed to the damage to pancreatic beta cells caused by Alloxan (Ali et al, 2011).…”
Section: -5-2 Alanine Aminotranseferase (Alt) Activitysupporting
confidence: 90%
“…The results of Table (4) showed a significant increase (P≤0.05) in the activity of the enzyme aminotransferase enzyme in the group of experimental diabetic rats (B), which reached 46.33 IU/l, compared with the intact control group (A), which was 21.67 IU/l, these results were consistent with what was mentioned by Mohammed et al, (2011) when they indicated a significant increase in the activity of the ALT enzyme compared to the intact control group. The cause of the increase in diabetic rats may be attributed to the damage to pancreatic beta cells caused by Alloxan (Ali et al, 2011).…”
Section: -5-2 Alanine Aminotranseferase (Alt) Activitysupporting
confidence: 90%
“…Five rats were isolated for control treatment (without infection), and the remaining rats were injected subcutaneously with Alloxan of Indian origin, which was prepared at the time of injection at a dose of 100 mg/kg of body weight. as it was dissolved by 1 gram of alloxan in 10 ml of physiological solution (normal saline) after starving the animals for 12 hours [19] and [20], decline after decline injection they were directly provided with food and the drinking water was replaced with a 5% glucose solution for a period of 24 hours to reduce the shock of the treatment decline [1]. After 72 hours, their blood sugar was checked using an Accu-Chek blood sugar test device of German origin to confirm that they had developed diabetes mellitus.…”
Section: Experiments Design 231 Induce Diabetes Mellitusmentioning
confidence: 99%
“…The remaining rats were injected subcutaneously with Alloxan of Indian origin, which was prepared at the time of injection at a dose of 100 mg/kg of body weight. as it was dissolved by 1 gram of alloxan in 10 ml of physiological solution (normal saline) after starving the animals for 12 hours [19] and [20], decline after decline injection they were directly provided with food and the drinking water was replaced with a 5% glucose solution for a period of 24 hours to reduce the shock of the treatment decline [1]. After 72 hours, their blood sugar was checked using an Accu-Chek blood sugar test device of German origin to confirm that they had developed diabetes mellitus.…”
Section: Experiments Design Induce Diabetes Mellitusmentioning
confidence: 99%